COVID-19 and its effect on income of different social groups in Vietnam: A comparative analysis - Trinh, Ha Anh; Do, Nguyen Duc (The Economics and Finance Letters, 2025)
This study examines the impact of COVID-19 on income distribution among different social groups in Vietnam, analyzing nominal and real income changes before, during, and after the pandemic. This study evaluates income growth across demographic and economic segments based on data from the General Statistics Office of Vietnam using comparative analysis and scatterplot diagrams. The findings show that COVID-19 disproportionately affected wealthier individuals, particularly those in urban areas leading to a decline in income inequality as measured by the GINI index. High-income regions experienced greater losses due to higher population densities and prolonged lockdowns. While lower-income groups maintained stable growth, overall income levels declined slowing economic recovery. Although income inequality narrowed, this resulted from economic contraction rather than improved wealth distribution. The study highlights the need for targeted policy measures to support economic resilience in high-density regions and mitigate income shocks during future crises.